2019
DOI: 10.1097/gox.0000000000002092
|View full text |Cite
|
Sign up to set email alerts
|

Fat Chance: The Rejuvenation of Irradiated Skin

Abstract: Summary:Radiotherapy (RT) helps cure and palliate thousands of patients with a range of malignant diseases. A major drawback, however, is the collateral damage done to tissues surrounding the tumor in the radiation field. The skin and subcutaneous tissue are among the most severely affected regions. Immediately following RT, the skin may be inflamed, hyperemic, and can form ulcers. With time, the dermis becomes progressively indurated. These acute and chronic changes cause substantial patient morbidity, yet th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 86 publications
(102 reference statements)
0
12
0
Order By: Relevance
“…The mechanisms by which ASCs promote fat graft vascularization are thought to be largely mediated via paracrine signaling. 4 Here, we…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The mechanisms by which ASCs promote fat graft vascularization are thought to be largely mediated via paracrine signaling. 4 Here, we…”
Section: Discussionmentioning
confidence: 95%
“…2,3 The adipose-derived stromal cells (ASCs) within the stromal vascular fraction (SVF) of fat are thought to drive these regenerative effects. 4 Evidence in support for this hypothesis has stemmed from several clinical and preclinical studies that demonstrate, compared to fat alone, grafts enriched with ASCs, also known as cellassisted lipotransfer, undergo less resorption and have improved vascularization and histological structure. [5][6][7] Recent work has indicated that ASCs are a heterogeneous population comprised of distinct subpopulations of cells with differing functional capacities; bone morphogenetic protein receptor (BMPR)-1A…”
Section: Introductionmentioning
confidence: 99%
“…Autologous fat grafting has gained acceptance to improve skin texture and postinflammatory hyperpigmentation associated with contour deformities of face (M. M. Bashir et al, 2019). Fat, being an autologous tissue, seems to be an ideal choice as filling material and is preferred owing to its abundant availability in areas like abdomen, buttocks, thighs, and arms without any significant donor site morbidity (Borrelli et al, 2019). Fat injection sessions can be repeated for further volume enhancement and fine‐tuning if needed (M. M. Bashir et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these proposed therapeutics include antioxidants like tocopherol targeting transforming growth factor beta, autologous fat transfer targeting fibroblast activity, and adipose‐derived stem cells which work through the release of growth factors and cytokines contributing to the mitigation of radiation‐damaged skin. 7 , 8 , 9 Although these therapies show clinical promise, to date, no single therapeutic option has been consistently effective in the management of CRF. 2 …”
Section: Introductionmentioning
confidence: 99%